Linoleic acid drives pulmonary lymphoepithelioma-like carcinoma progression via PPAR-α/TF axis - Bao, Hejing; Zhang, Jiani; Chen, Zhuoyan; Wang, Yuhuan; Wang, Zhe; Chen, Zhiting; Jiang, Ting; Zhang, Baishen; Zeng, Wen; Bao, Hehong; Ma, Shudong (Frontiers in Oncology, 2025)
BackgroundPrimary pulmonary lymphoepithelioma-like carcinoma (pLELC) is a rare subtype of non-small cell lung cancer(NSCLC) with unclear etiological mechanisms. This study aimed to investigate the underlying molecular mechanisms and therapeutic targets for pLELC.MethodsRetrospectively collected samples from advanced pLELC patients underwent proteomic and metabolomic analyses, and patient-derived xenograft (PDX) models were established for validation. Data-independent acquisition (DIA) quantitative proteomics revealed upregulated tissue factor (TF) protein expression in pLELC, while untargeted metabolomics identified key metabolites such as linoleic acid (LA).ResultsResults demonstrated that LA promotes tumor progression by facilitating M2-type tumor-associated macrophage infiltration and suppressing natural killer (NK) cell activity, effects reversible by the TF inhibitor Tisotumab. Mechanistic studies indicated that LA enhances TF expression via peroxisome proliferator-activated receptor α (PPAR-α), and TF inhibitors effectively counteract LA-induced malignant phenotypes.ConclusionThis study reveals that LA remodels the pLELC tumor microenvironment through the PPAR-α/TF axis, suggesting TF as a potential therapeutic target for pLELC.